EP80317 Restrains Inflammation and Mortality Caused by Scorpion Envenomation in Mice - Zoccal, Karina F.; Gardinassi, Luiz G.; Bordon, Karla C. F.; Arantes, Eliane C.; Marleau, Sylvie; Ong, Huy; Faccioli, Lúcia H. (Frontiers in Pharmacology, 2019)
Over 1 million cases of scorpion stings are estimated every year, whereas current treatment is limited to antivenom serum combined with supportive therapy. Tityus serrulatus scorpion venom (TsV) is composed by diverse molecules, including toxins that induce a catecholamine storm and mediate classical symptoms of scorpion envenomation. However, the same toxins promote an intense inflammatory response coordinated by innate immune cells, such as macrophages, contributing significantly to the lung edema and mortality caused by TsV injection. Macrophages sense TsV via innate immune receptors, including TLR2, TLR4 and CD14 that promote inflammation and mortality via PGE2/cAMP/PKA/NF-κB/IL-1β axis. The scavenger receptor CD36 also recognizes TsV, but in contrast to the other receptors, it drives the production of leukotriene B4 (LTB4). This lipid mediator operates via BLT1 receptor to reduce cAMP production and consequently IL-1β release, which results in resistance to fatal outcomes of experimental scorpion envenomation. EP80317 is an hexapeptide that serves as a ligand for CD36 and features protective effects under conditions such as atherosclerosis and vascular inflammation. In this study, we evaluated the effects of EP80317 treatment during experimental scorpion envenomation. EP80317 treatment suppressed mouse peritoneal macrophage production of interleukin-1β (IL-1β), IL-6, tumor necrosis factor (TNF-α), CCL3 and prostaglandin E2 in vitro. EP80317 treatment also boosted the production of LTB4 and IL-10 in response to TsV. Importantly, EP80317 restrained lung inflammation and mortality caused by TsV in vivo. Taken together, these data indicate a strong therapeutic potential of EP80317 as a supportive treatment to control inflammation induced by scorpion envenomation.